2009
DOI: 10.1084/jem.20082480
|View full text |Cite
|
Sign up to set email alerts
|

CD1c bypasses lysosomes to present a lipopeptide antigen with 12 amino acids

Abstract: The recent discovery of dideoxymycobactin (DDM) as a ligand for CD1a demonstrates how a nonribosomal lipopeptide antigen is presented to T cells. DDM contains an unusual acylation motif and a peptide sequence present only in mycobacteria, but its discovery raises the possibility that ribosomally produced viral or mammalian proteins that commonly undergo lipidation might also function as antigens. To test this, we measured T cell responses to synthetic acylpeptides that mimic lipoproteins produced by cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 68 publications
3
43
0
Order By: Relevance
“…The titer and extent of inhibition was similar to that of the known CD1a-presented ligand, sulfatide, and is similar to the recently observed effects of CD1c-presented ligands (supplemental Fig. S10, B and C) (49).…”
Section: Isolation Of Individual Molecularsupporting
confidence: 62%
“…The titer and extent of inhibition was similar to that of the known CD1a-presented ligand, sulfatide, and is similar to the recently observed effects of CD1c-presented ligands (supplemental Fig. S10, B and C) (49).…”
Section: Isolation Of Individual Molecularsupporting
confidence: 62%
“…This effect may be antigen specific, since N-MPR required liposome attachment, via either an NTA linkage or a covalent conjugation, to elicit an antibody response. The greater serum antibody titers induced by covalent antigen attachment could be explained by a benefit in antigen processing downstream of particulate association and internalization or by stimulation of innate pattern recognition receptors (38,46). Indeed, we have found that the structure of the lipid anchor dramatically affected the serum IgG response to liposomal N-MPR lipopeptides despite complete retention of all antigens in the liposome formulation (47).…”
Section: Discussionmentioning
confidence: 75%
“…An alternative pathway to the phagosome mediated by sortilin could represent another level of regulation during the development of the immune response. For example, some lipid antigens are loaded into CD1c molecules that bypass the lysosomal compartment (Van Rhijn et al, 2009).…”
Section: Discussionmentioning
confidence: 99%